Understanding personality pathology in a clinical sample of youth: study protocol for the longitudinal research project ‘APOLO’ - Nagila Koster; Igor Lusin; Paul T van der Heijden; Odilia M Laceulle; Marcel A G van Aken (BMJ Open)
Introduction We propose that a dimensional, multilayered perspective is well suited to study maladaptive personality development in youth. Such a perspective can help understand pathways to personality pathology and contribute to its early detection. The research project ‘APOLO’ (a Dutch language acronym for Adolescents and their Personality Development: a Longitudinal Study) is designed based on McAdams’ integrative three-layered model of personality development and assesses the interaction between dispositional traits, characteristic adaptations, the narrative identity and functioning.Methods and analysis APOLO is a longitudinal research project that takes place in two outpatient mental healthcare centres. Participants are youth between 12 years and 23 years and their parents. Data collection is set up to build a data set for scientific research, as well as to use the data for diagnostic assessment and systematic treatment evaluation of individual patients. Measurements are conducted half-yearly for a period of 3 years and consist of self-report and informant-report questionnaires and a semistructured interview. The included constructs fit the dimensional model of personality development: maladaptive personality traits (dispositional traits), social relations, stressful life events (characteristic adaptations), a turning point (narrative identity) and functioning (eg, achievement of youth specific milestones). Primary research questions will be analysed using structural equation modelling.Ethics and dissemination The results will contribute to our understanding of (the development of) personality pathology as a complex phenomenon in which both structural personality characteristics as well as unique individual adaptations and experiences play a role. Furthermore, results will give directions for early detection and timely interventions. This study has been approved by the ethical review committee of the Utrecht University Faculty for Social and Behavioural Sciences (FETC17-092). Data distribution will be anonymous and results will be disseminated via communication canals appropriate for diverse audiences. This includes both clinical and scientific conferences, papers published in national and international peer-reviewed journals and (social) media platforms.